Physical activity trajectories and subsequent fall risk: ARIC Study - Pettee Gabriel, Kelley; Griswold, Michael E.; Wang, Wanmei; Conway, Sadie H.; Windham, B. Gwen; Palta, Priya; Kucharska-Newton, Anna; Pompeii, Lisa A. (Preventive medicine, 2019)
To examine the impact of moderate to vigorous intensity physical activity (MVPA) trajectories during midlife and older adulthood with subsequent fall risk in later life. Cross-temporal analyses were conducted in 15,792 participants (27% black, 55% women) aged 45 to 64 years enrolled in the Atherosclerosis Risk in Communities (ARIC) Study. MVPA was collected at Exams 1 (1987–89), 3 (1993–95) and 5 (2011–13) using the ARIC/Baecke questionnaire. Latent class growth analysis was used to identify the MVPA trajectory groups. Reported falls outcomes were collected in 2013–14, 2015–16, and 2016–17. Generalized Linear Models were used to estimate associations of baseline predictors with trajectory class membership, as well as associations of trajectory classes with any falling (adjusted incident relative risks, aIRR) and with number of falls (adjusted relative rates, aRR). Four primary trajectory classes emerged, reflecting longitudinal patterns of maintained high (48%), maintained low (22%), increasing (14%) and decreasing (15%) MVPA. After adjustment for covariates, the decreasing MVPA trajectory group had a 14% higher risk of reporting any falling compared to the maintained high MVPA group [aIRR = 1.14 (1.01, 1.28)]. When compared to the maintained high MVPA group, the maintained low and decreasing group had a 28% [aRR = 1.28 (1.14, 1.44)] and 27% [aRR = 1.27 (1.17, 1.38)] higher rate in the reported number of falls, respectively. Findings support public health campaigns targeting habitual MVPA or exercise for fall prevention and suggest that interventions should be initiated in midlife; a time when individuals may be more able and willing to change behavior. •Few studies have characterized physical activity from midlife to older adulthood.•Physical activity from midlife to older adulthood can reduce fall risk.•Findings support public health campaigns centered on physical activity promotion.